ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI GELOMBANG BAGI SISWA SEKOLAH DASAR - Rahimatu Riska; Indah Syahrani (Kampus Akademik Publiser, 2025)
This research is motivated by students' low understanding of wave material in Natural and Social Sciences (IPAS) learning at the elementary school level. One cause is the suboptimal use of learning media that are appropriate to the material's characteristics and student needs. This study aims to analyze the effectiveness of IPAS learning media on wave material for fifth-grade students at SD Negeri 056018 Kampung Bamban, Jalan Batang Serangan, Sei Bamban Village. The method used was descriptive quantitative, with data collection techniques through questionnaires, observation, and documentation. The study subjects were 28 students. The results showed that the use of a variety of learning media such as animations, simulation videos, and real-life props significantly improved students' understanding of the concept of waves. These media were considered to help make the learning process more active, enjoyable, and understandable. This study recommends that teachers utilize interactive learning media more effectively and that schools provide facilities and training that support technology-based learning processes to optimize student learning outcomes.